PENGARUH E-WOM, KUALITAS LAYANAN TERHADAP CITRA DESTINASI BERDAMPAK PADA MINAT KUNJUNG WISATAWAN KE THE PICAS ADVENTURE BANJARNEGARA - Setijadi Setijadi; Ghonimah Zumroatun Ainiyah (STIE Pelita Nusantara Semarang, 2022)
Tourism is one of the sectors that can encourage the economy of a region. Managers of tourist destinations must be able to compete to be able to attract domestic tourists and foreign tourists in order to encourage the interest of visiting tourists to visit again. This study aims to determine the effect of electronic word of mouth, service quality on the image of a destination that can have an impact on tourist interest in The Picas Adventure Banjarnegara. The population in this study were all visitors to The Picas Resort in Banjarnegara. The number of samples used in this study were 722 people using a non-probability sampling technique through a purposive sampling approach. Methods of data collection using documentation and questionnaires. Instrument testing is done by testing the validity and reliability test. Data analysis used classical assumption test and hypothesis test (t test) with SPSS statistic version 24.The results showed that the variable electronic word of mouth, and service quality had a significant effect on the image of the destination, and the image of the destination had a significant effect on visiting interest. The conclusion of this study is that electronic word of mouth and service quality can improve the image of destinations with the presence of electronic word of mouth, so the development of digital promotion and marketing with E Commerce includes galleries, tourist routes, electronic reservations and other communication media can make consumers feel satisfied and clear on the information provided by The Pikas Adventure, and with the provision of services considered good and satisfying that exceeds consumer expectations can improve the image of the tourist destination. So that the existence of a good destination image will increase the interest of tourists to visit again. The manager is advised to maintain and improve electronic word of mouth which has been done through social media, maintain the image of the destination by providing complete packages, affordable prices, increasing cooperation in the field of tourism, and increasing marketing and promotion.